The Effect of Red Ginger Decoction Administration on the Reduction of Dysmenorrhea Pain among Female Adolescents at Nusantara Private Senior High School, Lubuk Pakam - Ika Nur Saputri; Gita Amelia (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Menstruation in adolescents is one of the indicators of biological maturity that occurs during puberty and signifies a woman’s readiness for pregnancy. Women’s reproductive health is influenced by various factors, including nutritional status and body weight. In addition, women often experience various menstrual-related problems, one of which is menstrual pain or dysmenorrhea. Dysmenorrhea is a common complaint among adolescent girls during menstruation and has the potential to interfere with daily activities. The use of natural ingredients, such as red ginger, is considered a relatively safe and effective alternative therapy for reducing pain without causing side effects associated with chemical medications. This study aimed to analyze the effect of administering red ginger decoction on reducing the level of dysmenorrhea pain among female adolescents at Nusantara Private Senior High School, Lubuk Pakam. This study employed a quasi-experimental design with a pretest–posttest approach involving 20 adolescent female respondents who experienced dysmenorrhea. Pain intensity was measured using a pain scale before and after the administration of red ginger decoction over several menstrual cycles. Data were analyzed using the Wilcoxon test to determine significant differences. The results of the Wilcoxon test indicated a significant reduction in pain (p = 0.000), with the mean pain score decreasing from 2.60 to 1.70 after the intervention. A total of 40% of respondents reported no pain after receiving the red ginger decoction. In conclusion, the administration of red ginger decoction has been proven effective in reducing dysmenorrhea pain among adolescent girls and can be considered a safe, practical, and natural alternative therapy.